Social media marketing, purchasing decisions, and consumer satisfaction in Peruvian millennials - Loza, Renzi (2026)
The accelerated growth of social media is largely driven by the active participation of the millennial generation. Their high  connectivity and digital habits have transformed these platforms into strategic channels for marketing and communication directed at this audience. In this context, the present study analyzes the effect of social media marketing on purchase decisions and customer satisfaction among Peruvian millennial consumers, with the aim of providing an in-depth understanding of online consumption patterns and offering valuable insights for the development of effective tailored business strategies. The results of the structural equation modeling (SEM), applied to a sample of 437 Peruvian millennials, reveal a positive effect of social media marketing on both purchase decisions and customer satisfaction. Entertainment, personalization, and service efficiency were also identified as having a significant influence on consumers' satisfaction. This study contributes to the current debate on digital marketing by enriching existing theories on millennial purchasing behavior in developing countries. The results have important implications for both the academic community and business practice. On the one hand, they inform policies directed at entrepreneurial initiatives targeting millennials; on the other, they guide companies in adapting their communication strategies to the needs of this specific market segment.